Low contact resistance in solid electrolyte-gated ZnO field-effect transistors with ferromagnetic contacts. Issue 1 (2nd December 2015) - Hu, Xiaotao; Sun, Jia; Qian, Chuan; Liu, Fangmei; Yang, Junliang; Guo, Guang-hua; Gao, Yongli
Abstract : We report on solid-electrolyte-gated FETs with ferromagnetic contacts that result in a decrease in contact resistance and assess their potential for spintronics. Abstract : Understanding the role of contacts and interfaces between ferromagnetic metals and semiconductors is a critical step for spin injection and transport. Here, high performance solid electrolyte gated ZnO field-effect-transistors (FETs) with ferromagnetic Co contacts as the source and drain electrodes were demonstrated. Solid electrolyte gating provides a large electric field in the FETs that leads to an ohmic contact between the Co electrode and the ZnO film. The contact resistance can be tuned by the gate voltage and reduced to 66 Ω cm. Compared with FETs using a traditional SiO2 dielectric, an improved transistor performance is achieved with a current on/off ratio of 10 6 and a field-effect mobility of 5.24 cm 2 V −1 s −1 . The magnetoresistance calculation based on a spin diffusion model indicates that the on-state contact resistance of the solid electrolyte gated FETs falls in the optimal range for the injection and detection of spin-polarized charge carriers. These results reveal that the electrolyte gating allows for engineering the contacts for nanoelectronic and spintronic devices.